2001
DOI: 10.1037/0022-3514.80.6.861
|View full text |Cite
|
Sign up to set email alerts
|

To do or not to do: Desirability and consistency mediate judgments of regret.

Abstract: In 4 studies, the authors demonstrated that when errors associated with action were inconsistent with decision nakers' orientation, they were undesirable and produced more regret than did errors associated with inaction. Conversely, when errors associated with action were consistent with decision makers' orientation. they were desirable and produced less regret than did errors associated with inaction. Desirability and consistency mediated this relationship, independent of mutability. These results were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 17 publications
9
78
0
Order By: Relevance
“…Our results supported our hypotheses and prior research for both hypothetical and realistic situations (e.g., Kuhl & Beckmann, 1994;Seta et al, 2001). Stateoriented individuals reported relatively high levels of regret and did not differ in regret responses regardless of whether the situation involved an action or inaction.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results supported our hypotheses and prior research for both hypothetical and realistic situations (e.g., Kuhl & Beckmann, 1994;Seta et al, 2001). Stateoriented individuals reported relatively high levels of regret and did not differ in regret responses regardless of whether the situation involved an action or inaction.…”
Section: Discussionsupporting
confidence: 82%
“…Prior research involving consistency and regret (e.g., Camacho et al, 2003;Connolly & Zeelenberg, 2002;Pieters & Zeelenberg, 2005;Seta et al, 2001) has found that, when actions/inactions are inconsistent with the decision maker's orientation (intention), relatively greater regret is felt than when they are consistent. Research in PSI theory has demonstrated that state-oriented individuals have difficulty regulating negative affect, are chronic worriers and are relatively unable to dispense with negative states.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown to be sensitive to a number of manipulations and can depend on such things as whether an action is consistent with a person"s personal orientation (Seta, McElroy & Seta, 2001) ,whether information about prior (Zeelenberg, van der Bos, van Dijk, & Pieters, 2002) or alternative (Ritov & Baron, 1995) outcomes is available to the decision-maker, whether an outcome is seen as reversible (Abendroth & Diehl, 2006), and whether the decisions being judged are presented in a within-or between-subjects design (N"gbala & Branscombe, 1997;Zhang, Walsh & Bonnefon, 2005). The action effect continues to be explored in scenario studies (Byrne & McEleney, 2000;Feeney & Handley, 2006;Walsh & Byrne, 2007;Zeelenberg, van der Bos, van Dijk & Pieters, 2002).…”
Section: Agency and Counterfactual Thinkingmentioning
confidence: 99%